Computational intelligence methods for bioinformatics and biostatistics : 10th International Meeting, CIBB 2013, Nice, France, June 20-22, 2013, Revised Selected Papers - Tagliaferri, Roberto; Wit, Ernst; Formenti, Enrico (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the 10th International Meeting on Computational Intelligence Methods for Bioinformatics and Biostatistics, CIBB 2013, held in Nice, France in June 2013. The 19 revised full papers presented were carefully reviewed and selected from 35 submissions. The papers are organized in topical sections on bioinformatics, biostatistics, knowledge based medicine, and data integration and analysis in omic-science.